As águas e a vida no imaginário dos pescadores - (:unkn) unknown (Universidade Federal do Amazonas, 2020)
The water environment is taken as the object of analysis of this research because it is the actor's field of action, the environment where the activity is carried out, the living environment that provides the fisherman's life and activity. As a central problem of the research, we seek to understand how the fishermen of the Maranhão community, in Parintins, through their narratives, express their worldview through the representations of the waters. Taking this investigative direction, we traced as a general objective to investigate how the fishermen of the Maranhã community in Parintins/AM, through their narratives, express their worldview in the water environment. As specific objectives, we first set out to understand the ways in which the traditional peoples of the Amazon elaborate their worldview. Second, to understand, through everyday narratives, how representations from the water environment structure the fishermen's worldview. The method used consisted of a qualitative bias with an open search and sensitive to the field of research divided into three stages. Initially with the survey of bibliographic data, the first trips to the research field, reformulation of the research project and elaboration of the first chapter of the dissertation for qualification. Then, in incursions into the field for data collection, in periodic trips throughout the years 2018, 2019 and 2020, making observations, notes in a field notebook and photographic records. Finally, we deal with the analysis of the narratives, and the elaboration of this dissertation document. The main theoretical basis comes from studies of the imaginary focusing on the concepts of Durand (1998) and Bachelard (1996). The main result indicated that the fishermen's worldview starts from an imaginary construction arising from the relationships experienced in their daily lives through their sensations, which develops their own cosmology, which involves their eco-socio-anthropo-cultural context.

El medio acuático se toma como objeto de análisis de esta investigación por ser el campo de acción del actor, el medio donde se desarrolla la actividad, el medio vivo que proporciona la vida y la actividad del pescador. Como problema central de la investigación, buscamos comprender cómo los pescadores de la comunidad de Maranhão, en Parintins, a través de sus narrativas, expresan su cosmovisión a través de las representaciones de las aguas. Tomando esa dirección investigativa, trazamos como objetivo general investigar cómo los pescadores de la comunidad de Maranhã en Parintins/AM, a través de sus narrativas, expresan su cosmovisión en el medio acuático. Como objetivos específicos, nos propusimos primero comprender las formas en que los pueblos tradicionales de la Amazonía elaboran su cosmovisión. En segundo lugar, comprender, a través de narrativas cotidianas, cómo las representaciones del medio acuático estructuran la cosmovisión de los pescadores. El método utilizado consistió en un sesgo cualitativo con una búsqueda abierta y sensible al campo de investigación dividido en tres etapas. Inicialmente con el levantamiento de datos bibliográficos, los primeros viajes al campo de investigación, reformulación del proyecto de investigación y elaboración del primer capítulo de la disertación de titulación. Luego, en incursiones de campo para la toma de datos, en viajes periódicos a lo largo de los años 2018, 2019 y 2020, realizando observaciones, apuntes en cuaderno de campo y registros fotográficos. Finalmente, nos ocupamos del análisis de las narrativas y de la elaboración de este documento de tesis. La principal base teórica proviene de los estudios del imaginario centrados en los conceptos de Durand (1998) y Bachelard (1996). El principal resultado indicó que la cosmovisión de los pescadores parte de una construcción imaginaria surgida de las relaciones experimentadas en su cotidiano a través de sus sensaciones, que desarrolla una cosmología propia, que involucra su contexto eco-socio-antropo-cultural.
Keywords: Semiótica; Simbolismo; CIÊNCIAS HUMANAS; IMAGINÁRIO; PROCESSOS SIMBÓLICOS; AMAZÔNIA; PESCADORES; COMUNIDADE DO MARANHÃO